FPGA IMPLEMENTATION OF INTELLIGENT EMBEDDED SYSTEM FOR DISTRIBUTED ELECTRICAL APPLIANCES - Vejendla, Swathi; Kamaraju, Dr. M. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Now a days, Technology is veryimportant in daily life. In the offices, theusage of electronic appliances is increasingrapidly. So the demand for power is alsoincreasing. The power demand can be metupto some extent by reducing powerwastage. The proposed system reducespower wastage by switching off theelectrical appliances when not in use. Theproposed system controls the appliancesautomatically based on the need and isimplemented on FPGA in Xilinx platformusing Verilog HDL.